Evaluasi Kelayakan Pamflet Berdasarkan Uji Keterbacaan oleh Masyarakat Sadar Wisata - Hidayat, Toni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to evaluate the feasibility of pamphlets used as an information medium for the aware tourism community, with a focus on readability testing. The readability test was conducted by 15 members of the tourism community who participated in this study. This study uses qualitative and quantitative evaluation methods to measure the level of understanding and comfort of the community with the information presented in the pamphlet. The results of the readability test show an overall average score of 79.34%, indicating that the pamphlet can be well understood by the tourism community. Based on these results, it can be concluded that this pamphlet is suitable for use without the need for revision, as it has met good readability standards. These findings contribute to the development of effective information media to raise public awareness of the importance of the tourism sector.